Relasi Kritis Antara Agama dan Negara - Nurul Fahmi (TASAMUH: Jurnal Studi Islam, 2015)
Political discourse is rising to the discourse of other Islamic thought, like theology. The history proved that politics is the first problem which is to be considered by Moslem, is political success. Also, this fhenomenon is to be base on rise of thought discourse on relation between nation and religion in the Moslem world. This condition shows that situation far from the spirit of al-Quran. Then, the main idea in this writing, namely; Specially relation between nation and religion, how does Islam view development? Focus of this writing is showong submain ideas, as; First, The Madinah’s nation, how did Muhammad Prophet act? The second, Then it is discoursed about how is the Islam nation position in the perspective of al-Quran This writing clames that the Moslems thought agreed that Islam and Moslem need nation. Islam wants shape social politic sociaty of Islam which high respecte fairness or social justice, and humanity values. The social order had happened in Madinah, in the Muhammad’s Prophet leadership.